2021
DOI: 10.1038/s41372-021-01023-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of evolving practices on SARS-CoV-2 positive mothers and their newborns in the largest public healthcare system in America

Abstract: Objective The impact of evolving guidelines and clinical practices on SARS-CoV-2-positive dyads across New York City Health and Hospitals during the early peak of COVID-19. Design A retrospective cohort study of positive-positive (P/P), positive-negative (P/N), and positive-untested (P/U) dyads delivered from March 1 to May 9, 2020. Wilcoxon rank sum, Chi-squared, and Fisher exact tests were used to analyze demographics, clinical variables, and system-wide management practices. Result A total of 2598 mothers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…On the contrary, Donati et al’s descriptive study [46] which focused on COVID positive mothers, reported a higher rate of mother-infant separation at birth (39%), a lower rate of skin-to-skin contact (26.6%) and rooming in with infant (72.1%), which align with the findings of Bartick and colleagues [36] that compared COVID positive with negative mothers. However, Maholtra [81] and Mayapoulos [39] did not find any difference in the rate of skin-to-skin contact between COVID positive and negative mothers. In Cojocaru’s study [86] , most COVID-positive mothers still opted to room in with their newborns and continue with skin-to-skin contact.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…On the contrary, Donati et al’s descriptive study [46] which focused on COVID positive mothers, reported a higher rate of mother-infant separation at birth (39%), a lower rate of skin-to-skin contact (26.6%) and rooming in with infant (72.1%), which align with the findings of Bartick and colleagues [36] that compared COVID positive with negative mothers. However, Maholtra [81] and Mayapoulos [39] did not find any difference in the rate of skin-to-skin contact between COVID positive and negative mothers. In Cojocaru’s study [86] , most COVID-positive mothers still opted to room in with their newborns and continue with skin-to-skin contact.…”
Section: Resultsmentioning
confidence: 78%
“…During the COVID period, more women favoured pharmacological pain relief measures such as epidurals [77] , [80] and received pethidine injections [79] . Between mothers who tested positive for COVID and those who tested negative, there was also no difference in the mode of birth [39] , [81] , [82] , induction, and use of epidural [39] , [82] .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous research has documented the decreased availability of lactation consultants during the pandemic, restriction of donor milk utilization, and a decrease in breastfeeding rates [9]. In contrast, Malhotra et al found breastfeeding to increase by hospitalized COVID-19-positive mothers [27]. One may speculate whether isolation and more peace and quiet could positively contribute when establishing breastfeeding.…”
Section: Breastfeedingmentioning
confidence: 99%
“…A survey from the United States reported that breastfeeding was lower in SARS-CoV-2-positive mothers than in the general population. 60 Such an outcome may be related to the early separation between mothers and neonates 61 and reduced lactation support during the pandemic. 62,63 Shorter breastfeeding duration was also associated with higher rates of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%